2012
DOI: 10.1080/0969594x.2012.668870
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a foundation for valid teacher judgement on student learning: the role of pre-service assessment education

Abstract: The purpose of this research was to explore changes in teacher candidates' confidence in assessment as a foundation for promoting valid teacher judgements on student learning. Based on a sample of 48 teacher candidates enrolled in a semester-long measurement course at one teacher education programme in Florida, this survey-based study provided evidence that teacher candidates can develop confidence in assessment whilst deepening their conceptions of assessment. The majority of teacher candidates expanded their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 16 publications
6
23
0
3
Order By: Relevance
“…Consistent with previous studies (DeLuca and Klinger, 2010;Siegel and Wissehr, 2011;DeLuca et al, 2012;Hill et al, 2013) this study indicates that having a university course or courses focused on assessment was beneficial in terms of teacher candidate formative assessment learning. In particular, this study confirms the findings of Buck et al (2010) that making formative practices explicit to teacher candidates by using them in university classrooms served to mitigate the tendency to use more traditional assessments such as tests but goes further in demonstrating that these teacher candidates understood and advocated for involving students as partners in the assessment process.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Consistent with previous studies (DeLuca and Klinger, 2010;Siegel and Wissehr, 2011;DeLuca et al, 2012;Hill et al, 2013) this study indicates that having a university course or courses focused on assessment was beneficial in terms of teacher candidate formative assessment learning. In particular, this study confirms the findings of Buck et al (2010) that making formative practices explicit to teacher candidates by using them in university classrooms served to mitigate the tendency to use more traditional assessments such as tests but goes further in demonstrating that these teacher candidates understood and advocated for involving students as partners in the assessment process.…”
Section: Discussionsupporting
confidence: 90%
“…In line with previous studies (DeLuca et al, 2012;Hill et al, 2013), having a classroom assessment course that teaches about such practices is important as well as intertwining formative assessment learning within other courses (Smith et al, 2014). Our participants confirmed that learning about including students in assessment by being included in it themselves in their university courses was helpful and, as evidenced, suggested that doing this more often in all courses would be helpful to their learning.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The first theme mainly focused on teachers' conceptions of assessment (CoA) purposes (e.g., Winterbottom et al, 2008;Deluca and Klinger, 2010;Brown and Remesal, 2012;Chen and Brown, 2013;Deluca et al, 2013a). For instance, using the Teachers' Conceptions of Assessment (TCoA) inventory for a cross-cultural comparison between pre-service teachers in New Zealand and in Spain, Brown and Remesal (2012) established a model for pre-service teachers' CoA, which comprises five different assessment purposes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This methodology is commonly used in previous studies on pre-service teachers or teachers' conceptions of assessments (Brown, Harris, and Harnett 2012;DeLuca, Chavez, and Cao 2013;Segers and Tillema 2011). The questionnaire consists of 20 items reflecting 4 constructs (AFL, AAL, AOF, and ACC).…”
Section: Methodsmentioning
confidence: 99%